PENGEMBANGAN MOTIF BATIK BERBASIS TINGGALAN ARKEOLOGI KELURAHAN LEGOK KOTA JAMBI TAHAP II - Nainunis Aulia Izza; Ari Mukti Wardoyo Adi; Nugrahadi Mahanani; Wulan Resiyani; Amor Seta Gilang Pratama (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2022)
This program is a continuation of the activities in the previous year. The newest batik motifs were inspired by ornaments and archaeological remains from the Situs Candi Solok Sipin. In 2020, batik tulis, the Makara Ekikarana motif has been produced. In 2021, the team try to make batik cap inspired by the Yaksa figure on the Makara and Stupa from the Situs Candi Solok Sipin. The batik cap is related to the purpose of preparing products at affordable prices, it's hoping that the batik is marketed more broadly. In addition, this new motif can also enrich the batik repertoire at the Rumah Batik Kelurahan Legok. The method is held in stages; the first stage is the preparation. During the preparation stage, we make motif design and make coordination with the Kelurahan Legok dan Rumah Batik. After the batik cap motif is ready, the next step is to make a stamp. After the preparation stage was completed, the next step is to produce a batik cap in 3 (three) days. On the last day, we make a product launch, the products are ready to be marketed. The results achieved include the creation of the Yaksa Stupa motif which is applied to cloth and masks.